ANALISIS DAN PROBLEMATIKA PERAN ORANG TUA DALAM MENDAMPINGI ANAK BELAJAR BAHASA INDONESIA PADA MASA PANDEMI COVID -19 - Arifin, Muchlis (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2021)
The Covid 19 pandemic problem is becoming a big problem for people or citizens of this part of the world. The government has handled various things in order to reduce and break the chain of the virus, such as maintaining distance, wearing a mask and always washing your hands after or before handling objects or shaking. The government strives to do this so that the chain of disease will end soon, but it is still difficult for the government to handle it by itself, there must be self-awareness in the community so that all diseases end. The impact and impact of this virus is enormous for the economy, education, and even people's livelihoods. The impact that concerns me the most is in the world of education, because everything is done from home while parents do not always understand the schoolwork given by the teacher. Parents also have their own busyness in earning a living and giving roles in their responsibilities as parents. In this study using a qualitative method that does not use numbers in data collection and providing interpretation of the results.Keywords: Covid-19, the role of parents, Indonesian language lessons.